Spatial and Temporal Diversity Variation in the Anopheles Communities in Malaria-Endemic Regions of Colombia (2023)
ABSTRACT: This study aimed to evaluate at a temporospatial scale, the influence of anthropogenic land cover changes in the Anopheles species community composition and diversity in two Colombian malaria-endemic regions, Bajo Cauca and Pacific. To determine variations over time, mosquitoes were collected in two time periods; land cover types were characterized on orthorectified aerial photographs, and landscape metrics were estimated for each locality and period. A temporal dissimilarity analysis to evaluated species replacement and the nestedness species loss/gain showed the influence of the species loss or gain component on Anopheles species assemblage (23%). The relationship between land cover variation and Anopheles beta diversity, evaluated by regression analysis, showed the effect of forest variation in the Anopheles community (bsim and forest 2 5 0.9323; bsne and forest r 2 5 0.9425). Furthermore, a canonical correspondence analysis showed that the land cover types associated with Anopheles species presence were bare soil, shrub, wet areas, and forest. Results demonstrated the impact of land cover changes attributed to human activities on Anopheles population dynamics, over time; this was evidenced as species loss or gain, which was specific to each locality. Notably, the main malaria vectors were dominant in most localities over time, suggesting their tolerance to anthropogenic transformations; alternatively, the environmental changes are providing adequate ecological conditions for their persistence. Finally, the data generated are relevant for understanding the impact that environmental change may have on the dynamics of the neotropical malaria vectors. Thus, this research has potential implications for vector control interventions.